New Approach to State Protection of Competition (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the article is to improve the possibilities for learning and applying practical tips on competition protection, and to develop ways to promote competition and economic growth that will enhance the prosperity of the economy and society. It is important that the goal of competition protection is to create conditions that will lead to a more competitive market structure and business behavior without direct intervention from the competition body. Note that the most disadvantageous alternative to the competition body is the application of close and lasting control of the dominant firms by competition law. This alternative results in more inadequate funding by requiring more resources. Modern economic reality, characterized by the transformation of economic relations, business globalization, integration of transitional economies into the global space, makes the development of competitive relationships more important for improving economic and innovation performance. As a result, it has been established that a successful market economy requires a competitive culture within the country. Both consumers and the business community need to be aware of their competitive policies and how they can benefit from it. Competition agencies play an important role in this learning process.